(untitled) (Research, Society and Development, 2021)
In order to understand the potential use of unconventional ingredients for the formulation of food products, this research aimed at developing food bars using co-product and by-products of the agro-industrial chain and evaluating their nutritional and sensory properties, as well as purchase intention. Four formulations were developed, being a standard food bar (F0) having as base ingredient a paste prepared with the co-product of the cashew peduncle and whey without the addition of sesame and three modifications of this formulation (F1, F2, F3) with addition of 5%, 10% and 15% sesame, respectively. The global acceptance of the formulations was assessed using a 9-point structured hedonic scale and the purchase intention was verified through a preference test ranked from 1 to 5 points. The results of the sensory tests showed that the average acceptance of the product was 6.24, and the F3 bar obtaining better marks in the purchase intention tests. For the color and firmness tests, the F3 formulation showed a higher ΔE, indicating a lighter color compared to the other formulations. In the evaluation for cutting force, the F0 formulation showed the best results, being characterized as firmer products. The study demonstrated that food bars can be produced from the use of co-product and by-products of the agro-industrial chain with satisfactory nutritional and sensory properties.